Aerobic sludge granulation for simultaneous anaerobic decolorization and aerobic aromatic amines mineralization for azo dye wastewater treatment - Yan, Lawrence K Q (Environmental technology, 2018)
In this study, the capability of using aerobic granules to undergo simultaneous anaerobic decolorization and aerobic aromatic amines degradation was demonstrated for azo dye wastewater treatment. An integrated acclimation-granulation process was devised, with Mordant Orange 1 as the model pollutant. Performance tests were carried out in a batch column reactor to evaluate the effect of various operating parameters. The optimal condition was to use 1.0-1.7 mm (1.51 ± 0.33 mm) granules, 5 g/L biomass, and 4000 mg/L organics as nutrient; and supplement the wastewater with 1  mg/L dissolved oxygen. This led to a dye mineralization of 61 ± 2%, an anaerobic dye removal of 88 ± 1%, and an aerobic aromatic amines removal of 70 ± 3% within 48 h. This study showed that simultaneous anaerobic/aerobic process by aerobic granules could be a possible alternative to the conventional activated sludge process